A Survey of the General Hospital Environment: Focusing on Pajama Design in a Japanese University Hospital. Issue 1 (2nd January 2023) - Imanishi, Sachiko; Ida, Mitsuru; Yagi, Naomi; Kawaguchi, Masahiko
Abstract: This study investigated nurses' and patients' perceptions of hospital room environment and patient pajama design. Nurses working in a Japanese university hospital and patients aged 20 and older were surveyed. Over 75% of patients rated the hospital environment and hospital rooms as "very good" or "good, " but less than one in three nurses rated them similarly. Patients were more likely than nurses to rate rental pajamas as "very good" or "good." Contrary to the nurses, only about one in four patients valued wearing well-designed pajamas. Nurses' and patients' perceptions differed regarding hospital pajamas, but not about improving hospital rooms.